A Study of the Life of Imam Asbat Bin Nasr Al-Hamdani (d. 170 AH) - may Allah have Mercy on him - (Islamic Sciences Journal, 2024)
This research is titled ((Study of the life of Imam Asbat bin Nasr Al-Hamdani (d. 170 AH) - may Allah have mercy on him)) and the goal is to explain the life of a narrator from among the most prominent followers of the Followers, may Allah  please  them.       He is considered one of the prominent commentators who conveyed the interpretation of the Mighty Book of Allah, and Imam Al-Tabari mentioned him, and the scholars approved  his interpretations. He is considered one of the prominent figures of the Iraqi school of Kufa, so I decided to present something about his life, as there is no independent study of him.
Keywords: Study, Asbat, Al-Hamdani, Imam, Nasr.